Single Subject Research: Implementasi Pembelajaran Berbasis Masalah terhadap Pemahaman Matematis Siswa - Ulfah, Alfiatun Fitriani; Prahmana, Rully Charitas Indra (Universitas Hamzanwadi, 2018)
This study aims to determine the factors of studentâs learning difficulties and the implementation of problem-based learning to studentâs mathematical understanding. Subjects in this study is the student of class VIII A SMP Muhammadiyah 6 Yogyakarta. The techniques of data collection used observation and interview to determine the factors of learning difficulties and evaluation methods to determine studentâs mathematical understanding ability. Type of research used is single subject research with basic design of A-B. The results of this study indicate that the studentâs learning difficulties experienced by students is caused by social factors that is from a classmate. Furthermore, problem-based learning can improve studentâs mathematical understanding. It can be seen from the average score obtained by the student before the treatment given that is 28.5 and increased to 94 after treatment.